Combination of pre-adapted bacteriophage therapy and antibiotics for treatment of fracture-related infection due to pandrug-resistant Klebsiella pneumoniae - Eskenazi, Anaïs; Lood, Cédric; Wubbolts, Julia; Hites, Maya; Balarjishvili, Nana; Leshkasheli, Lika; Askilashvili, Lia; Kvachadze, Leila; van Noort, Vera; Wagemans, Jeroen; Jayankura, Marc; Chanishvili, Nina; et al. (Nature communications, 2022)
A 30-year-old bombing victim with a fracture-related pandrug-resistant Klebsiella pneumoniae infection after long-term (>700 days) antibiotic therapy is treated with a pre-adapted bacteriophage along with meropenem and colistin, followed by ceftazidime/avibactam. This salvage therapy results in objective clinical, microbiological and radiological improvement of the patient’s wounds and overall condition. In support, the bacteriophage and antibiotic combination is highly effective against the patient’s K. pneumoniae strain in vitro, in 7-day mature biofilms and in suspensions. In this case study of a patient with fracture-related pandrug-resistant Klebsiella pneumoniae infection after long-term antibiotic therapy, the authors use a combination therapy of pre-adapted bacteriophage and antibiotics resulting in clinical, microbiological and radiological improvement.